Exploring the Potential of PEEK in Prosthetic Dentistry: A Contemporary Perspective - Sreenivasulu, Duggineni; Sowjanya, J Lakshmi (International Journal of Dental Materials, 2024)
There has been ongoing research to find ideal restorative materials for replacing lost dentofacial structures. Advances in dental materials have provided dentistry with more promising options. Oral conditions require a material with good mechanical, biological and aesthetic properties. Polyetheretherketone (PEEK) is currently one of the viable materials approved by science for restoring lost orofacial tissues. PEEK is a polycyclic, aromatic, thermoplastic polymer with a semi-crystalline and linear structure. It has good mechanical and electrical properties, including resistance to high temperatures and hydrolysis. Its high biocompatibility has led to increased use in orthopaedic and trauma cases. PEEK is a respected dental material and is increasingly replacing metal components in various applications. The polymer has been used in medical devices for decades and offers an impressive range of properties suitable for medical use. Due to its excellent properties, PEEK has several applications in dentistry, including implants, removable and fixed partial dentures, and orthodontic wires. This article explores the potential applications of PEEK in Prosthodontics.